THE SYSTEM OF SUBJECTS ENSURING THE REGIME OF MARTIAL STATE IN THE STATE AND THE LOCATION AND CHARACTERISTICS OF MILITARY STATE ADMINISTRATIONS IN IT (Bulletin of criminological association of Ukraine, 2024)
It is emphasized that the subjects of ensuring the legal regime of martial law in Ukraine are a set of specially authorized bodies of state power (represented by their officials), which, in accordance with the norms of the current legislation, are endowed with a special legal status (a set of special subjective rights and legal obligations relations), which gives them the opportunity to implement various legal, organizational, material and technical, informational, financial and economic and other means aimed at forming and maintaining conditions for the effective functioning of the relevant legal regime. It is argued that today there are many subjects of martial law enforcement in Ukraine, which are quite diverse in terms of their legal status, but actively interact with each other in the process of performing functional tasks. Each of them has its own legal role in creating and maintaining the working conditions of the studied legal regime. It is substantiated that the difference between military administrations and other subjects is that they are authorized to ensure not only the conditions and other aspects of the functioning of the martial law mechanism as a whole, but also the process of implementing the measures of this legal regime, provided for by the Law of Ukraine "On the Legal Regime of Martial Law ". This unique feature testifies to the concentration in the legal status of military administrations of all the fullness of public power within the territory where the legal regime of martial law has been introduced, because they are responsible for both the surrounding organization of the latter and the practical implementation of its mechanism.
Keywords: martial law; legal regime; legal status; subjects; military administrations